The Relationship Between Body Mass Index (BMI) and the Risk of Type 2 Diabetes Mellitus Among Adults: A Case Study from Gasr Al-Akhyar – Libya - Altaher Abdulwahid Aljeheimi; Saleh Mohammed Biki (Journal of Libyan Academy Bani Walid, 2025)
Obesity is considered one of the most serious and widespread diseases of the modern era. Body Mass Index (BMI) is one of the principal indicators used to assess overweight and obesity. Data were collected from 100 randomly selected cases at the Primary Health Care Center in Gasr Al-Akhyar, Libya. Using standardized measurements, the relationship was analyzed through Pearson’s correlation coefficient via SAS software. The results revealed a statistically significant correlation between obesity and diabetes, particularly within the age group of 50–59 years, confirming the importance of weight control in preventing diabetes and its associated complications. This study aims to examine the relationship between elevated Body Mass Index and Type 2 Diabetes Mellitus among a sample of patients attending the Primary Health Care Center in Gasr Al-Akhyar.